REAL as an Instructional Design Teaching Models: Pre-service Teachers’ Satisfaction - Armandani, Karina; Fauzazillah, Fauzazillah; Puspitasari, Ayu; Kusriandi, Wendi; Aisyah, Aisyah (Universitas Pahlawan Tuanku Tambusai, 2025)
Preservice teachers often face challenges in designing instructional plans that are coherent, goal-oriented, and adaptable to diverse student needs. Although various instructional design models exist, their practical use remains limited. This study explores the application of the REAL (Review, Elaborate, Apply, Lead-up) model and Universitas Swadaya Gunung Jati. Using a qualitative approach, data were collected through questionnaires and unstructured interviews. Results show that the REAL model supports systematic and practical instructional design, with a satisfaction score of 2.70 indicating positive responses. Interviews further reveal increased confidence and clarity among preservice teachers. This model is recommended for use as a practical framework in the design of teaching instruction and is suggested for further evaluation to enhance its scalability and impact across different educational contexts.